Internalization of human rights, sustainability and the principle of the dignity of the human person in the consumer relationship (Research, Society and Development, 2022)
The concern with the inexhaustible use of natural resources is a major problem in the world scenario. This article aims to analyze the internalization of the promotion of Human Rights, the construction of effective Sustainability and the protection of the principle of Dignity of the Human Person, in the consumption relationship, by seeking to conserve the environment for present and future generations. For the approach, the hypothetical-deductive method and qualitative descriptive research based on bibliographic and documental survey will be used. The result is that the unbridled consumption relationship affects society in the social, political, environmental and economic spheres, thus requiring changes in habits, thoughts and attitudes that promote consumer control, aiming at a fair, balanced and ecologically sustainable society.